203k views
4 votes
Solve the decay equation y' = -ky using the integrating factors method. Show work

User Varantir
by
6.1k points

1 Answer

4 votes

Answer:


y=(c)/(e^(kx))

Explanation:


\frac{\mathrm{d} y}{\mathrm{d} x} =-ky


\frac{\mathrm{d} y}{\mathrm{d} x} +ky=0

comparing with equation


\frac{\mathrm{d} y}{\mathrm{d} x} + Py=Q(x)


I.F.= e^(\int P dx)


I.F.= e^(\int k dx)


I.F.= e^(kx)


y=(1)/(I.F.) ( \int {Q(x)}  dx  +c)


y=(1)/(e^(kx)) ( \int {0}  dx  +c)


y=(c)/(e^(kx))

User Nguyen Hoan
by
5.8k points